Analisis Pendapatan dan Bagi Hasil Antara Tauke dan Nelayan Purse Seine di Kecamatan Teluk Nibung Kota Tanjung Balai Provinsi Sumatera Utara - Immanuel Benaya Sitanggang; Lamun Bathara; Eni Yulinda (Jurusan Sosial Ekonomi Perikanan, 2021)
The study aims to find out the amount of revenue, analyze the yield-share system of purse seine fishermen and compare between local revenue share and government regulations. The research method used in this study is the survey method, while the determination of the respondents of the purse seine fishermen is done by the census method, which is by making all the owner fishermen into respondents who number 11 people. Based on the results of research and analysis that has been conducted obtained that the total net income of purse seine fishermen in a month in the peak season ranges from IDR. 149,780,555.46, in the current season ranges from IDR. 107,775,782.74. The profit-share system implemented in Teluk Nibung sub-district is 50% of the net proceeds minus the fixed cost for the owner's fishermen and 50% for labor fishermen from the net proceeds, with the agreement of operational costs being jointly dependent. This joint dependent has been agreed between the owner's fisherman and the labor fisherman which is a hereditary rule from a long time ago. The result-sharing system implemented already complies with law No.16 of 1964 on Fishery Sharing, which if used motorboats at least 40% of the net yield for labor fishermen, while in Teluk Nibung sub-district more than 40% is distributed to labor fishermen which is 50%.